2019
DOI: 10.1021/acs.jpclett.9b01220
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Noncovalent Interactions Facilitate Thermally Activated Delayed Fluorescence (TADF)

Abstract: In the conventional molecular design of thermally activated delayed fluorescence (TADF) organic emitters, simultaneously achieving a fast rate of reverse intersystem crossing (RISC) from the triplet to the singlet manifold and a fast rate of radiative decay is a challenging task. A number of recent experimental data, however, point to TADF emitters with intramolecular π–π interactions as a potential pathway to overcome the issue. Here, we report a comprehensive investigation of TADF emitters with intramolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…The key transition constants of DBFDPO: x % TArDFTPPO films are estimated with Equations to quantitatively figure out the influence of intermolecular interactions on TADF performance:1c kPF=ηPFτPF =knormalrnormalSηPF kDF=ηDFτDF kISC=ηDFηPL kPF kRISC=ηDFηPF kDFkPFkISC in which k PF , k DF , k ISC , k RISC, and knormalrnormalS are rate constants of PF and DF8, intersystem crossing (ISC) and RISC processes, and singlet radiation, respectively; η PF and η DF are PF and DF quantum efficiencies, respectively (Figure d and Table S2, Supporting Information). It indicates that the k RISC and k DF of the films are in direct proportion to x % in the range of 1–80%, owing to the Δ E ST reduction and multichannel RISC process induced by the intermolecular CT effect . Differently, k PF and knormalrnormalS rapidly decrease when x % increasing from 1% to 10%, but shapely increase when x % further increasing to 80%.…”
Section: Resultsmentioning
confidence: 88%
“…The key transition constants of DBFDPO: x % TArDFTPPO films are estimated with Equations to quantitatively figure out the influence of intermolecular interactions on TADF performance:1c kPF=ηPFτPF =knormalrnormalSηPF kDF=ηDFτDF kISC=ηDFηPL kPF kRISC=ηDFηPF kDFkPFkISC in which k PF , k DF , k ISC , k RISC, and knormalrnormalS are rate constants of PF and DF8, intersystem crossing (ISC) and RISC processes, and singlet radiation, respectively; η PF and η DF are PF and DF quantum efficiencies, respectively (Figure d and Table S2, Supporting Information). It indicates that the k RISC and k DF of the films are in direct proportion to x % in the range of 1–80%, owing to the Δ E ST reduction and multichannel RISC process induced by the intermolecular CT effect . Differently, k PF and knormalrnormalS rapidly decrease when x % increasing from 1% to 10%, but shapely increase when x % further increasing to 80%.…”
Section: Resultsmentioning
confidence: 88%
“…Recent studies have shown that this type of linkage disfavors intermolecular π-π stacking among TADF molecules, and simultaneously enhances spinorbit couplings between the S 1 and T 1 states. [48,51,52] These molecular features of ortho-linked donor/acceptor TADF molecules can help not only improve the rates of RISC processes for fast singlet-exciton generation in TADF molecules, but also suppress the formation of intermolecular aggregate states as well as the need for a host material, which all can improve IQEs in hyperfluorescence-based devices. Excitation energy-transfer calculations show that the Förster mechanism leads to efficient energy transfer from 4CzDPO to TBPe.…”
Section: Discussionmentioning
confidence: 99%
“…In each of the materials, the HOMO was seen to be dispersed over the benzofurocarbazole electron‐donating group, with the LUMO predominantly dispersed over the diphenyltriazine electron‐acceptor moiety. The n‐π* electron interaction between the triazine moiety and the non‐bonding electron of nitrogen in benzofurocarbazole is also similar in all three TADF phenyl linkers . The dihedral angles between the phenyl linker and diphenyltriazine moiety in the three compounds were calculated to lie in the narrow range of 35–38°.…”
Section: Resultsmentioning
confidence: 84%
“…In each of the materials, the HOMO was seen to be dispersed over the benzofurocarbazole electron-donatingg roup, with the LUMO predominantly dispersed over the diphenyltriazine electron-acceptor moiety.T he n-p*e lectron interaction between the triazine moiety andt he non-bonding electron of nitrogen in benzofurocarbazole is also similar in all three TADF phenyll inkers. [40] The dihedrala ngles betweent he phenyl linker and diphenyltriazine moiety in the three compounds were calculated to lie in the narrow range of 35-388.T he LUMO energy levels were also calculated to be similar in the three compounds. On the other hand, the dihedrala ngles be- DFT calculation results obtained by using the Gaussian 16 softwarea re basedo nt he B3LYP 6-31G* basis set.…”
Section: Resultsmentioning
confidence: 98%